Aniline trimer based chemical sensor for dual responsive detection of hazardous CN¯ ions and pH changes. (May 2019) - Reddy, P. Madhusudhana; Hsieh, Shih-Rong; Lee, Ming-Ching; Chang, Chi-Jung; Pundi, Arul; Chen, Yi-Shao; Lu, Chien-Hsing; Yeh, Jui-Ming
Abstract: It is still a challenging task to make a colorimetric sensor which can respond to multiple responses at the same time. This task is even more difficult in aqueous solutions, as water molecules will significantly interfere the sensing process. Therefore, we have designed the low-cost, simple, efﬁcient and selective dual responsive chemical sensor (DRCS) by capping the aniline trimer with benzoyl isothiocyanate. This sensor combines the advantages of naked eye detection of the CN¯ ion at different pH values. Moreover, DRCS can detect the pH of mixed solvent (DMSO/H2 O) by the naked eye. The DRCS has shown high sensitivity to CN¯ ions. Meanwhile, it has no obvious response to other interfering anions, such as F¯, AcO¯, Br¯, HSO4 ¯, SCN¯, PO4 3 ¯, I¯, ClO4 ¯, Cl¯, NO3 ¯, PF6 ¯, and BF4 ¯. A minimum detection limit of 0.2 μM was achieved by DRCS for CN¯ ions. The feasibility of on-site detection of CN¯ was demonstrated using DRCS coated filter paper stripes. The present study reveals that the DRCS as low-cost material can be used as a potential sensor for the selective sensing of CN¯ ions and pH in the solutions. Graphical abstract: Image 1 Highlights: Dual responsive chemical sensor (DRCS) was synthesized by capping aniline trimer with benzoyl isocyanate. The sensor, DRCS was explored to detect the CN¯ anions and pH values by naked eye. Detection of CN¯ byDRCS was also monitored by UV–vis, NMR, and colorimetric techniques. Simple, rapid, and cost effective paper "test stripes" ofDRCS can monitor the CN¯ in aqueous solution. DRCS has an excellent sensitivity with the detection limit up to 0.2 μM.